2023
DOI: 10.2337/dc23-0036
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and the Development of Islet Autoimmunity and Type 1 Diabetes in 5- to 15-Year-Old Children Followed in the TEDDY Study

Abstract: OBJECTIVE This study investigated physical activity and its association with the development of islet autoimmunity and type 1 diabetes in genetically at-risk children aged 5–15 years. RESEARCH DESIGN AND METHODS As part of the longitudinal Environmental Determinants of Diabetes in the Young (TEDDY) study, annual assessment of activity using accelerometry was conducted from age 5 years. Time-to-event analyses using Cox proport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…If time passes with no diagnosis of stage 3 type 1 diabetes, cognitions about type 1 diabetes may change and individuals may become convinced they will never get the disease or have reduced risk, despite evidence to the contrary [137]. Parents often engage in behaviours in attempts to prevent type 1 diabetes when faced with the news that their child is at increased risk, even when not provided with recommendations to do so, though more-recent data have shown that lower physical activity and meal plans with a higher glycaemic index are associated with faster progression to type 1 diabetes [138][139][140]. Meal-planning changes are most commonly reported, with extra monitoring at home (including blood glucose checking) being particularly common in families with someone who already has type 1 diabetes [141,142].…”
Section: Psychosocial Supportmentioning
confidence: 99%
“…If time passes with no diagnosis of stage 3 type 1 diabetes, cognitions about type 1 diabetes may change and individuals may become convinced they will never get the disease or have reduced risk, despite evidence to the contrary [137]. Parents often engage in behaviours in attempts to prevent type 1 diabetes when faced with the news that their child is at increased risk, even when not provided with recommendations to do so, though more-recent data have shown that lower physical activity and meal plans with a higher glycaemic index are associated with faster progression to type 1 diabetes [138][139][140]. Meal-planning changes are most commonly reported, with extra monitoring at home (including blood glucose checking) being particularly common in families with someone who already has type 1 diabetes [141,142].…”
Section: Psychosocial Supportmentioning
confidence: 99%
“… 55 The screening effort also allow the identification of stage 1 individuals to develop methods to prevent them from progressing to stage 2. The screening effort should also include stage 2 type 1 diabetes individuals who would be eligible to life style intervention 56 or FDA approved Teplizumab treatment 57 to delay the onset of stage 3 type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%